2015
DOI: 10.1111/echo.13093
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Future Atrial Fibrillation Development in Patients with Hypertrophic Cardiomyopathy: A Prospective Follow‐Up Study

Abstract: In patients with HCM, LA phasic functions, PWD, and NT-proBNP levels predict future development of AF. Assessment of LA phasic functions during routine echocardiographic evaluation and measuring NT-proBNP levels and PWD values of patients with HCM during daily practice may provide important data in predicting those at high risk of AF occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
4
10
0
3
Order By: Relevance
“…23,24 This is consistent with our observation that left atrial size was an independent predictor of incident AF. It has also been shown that age and congestive symptoms are independent predictors of AF occurrence.…”
Section: Discussionsupporting
confidence: 92%
“…23,24 This is consistent with our observation that left atrial size was an independent predictor of incident AF. It has also been shown that age and congestive symptoms are independent predictors of AF occurrence.…”
Section: Discussionsupporting
confidence: 92%
“…Atrial enlargement implies loss of normal architecture and generation of new electric circuits that predispose to the development of AF. This finding has been repeated in several studies using atrial dimension instead of atrial area . Our study is the first to consider a cutoff value for the atrial area, a parameter that is much more used in clinical practice than atrial dimension.…”
Section: Discussionsupporting
confidence: 62%
“…This finding has been repeated in several studies using atrial dimension instead of atrial area. 1,4,16,17 Our study is the first to consider a cutoff value for the atrial area, a parameter that is much more used in clinical practice than atrial dimension. The value of 28 cm 2 was found a good parameter to predict the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic Cardiomyopathy: PWD together with LA phasic functions, and N-Terminal Pro-Brain Natriuretic Peptide (NT-proBNP) levels, predict development of AF [22].…”
Section: Normal Limit Values Of P-wave Dispersion (Pwd)mentioning
confidence: 99%